Hydrothermal Synthesis of ZnWO4 Hierarchical Hexangular Microstars for Enhanced Lithium‐Storage Properties. Issue 3 (24th January 2017) - Shi, Nianxiang; Xiong, Shenglin; Wu, Fangfang; Bai, Jing; Chu, Yanting; Mao, Hongzhi; Feng, Jinkui; Xi, Baojuan
Abstract : ZnWO4 hierarchical hexangular microstars (HHMs) composed of crossed microplatelets were synthesized by a two‐step hydrothermal reaction without using any surfactants. The homogeneous HHMs were characterized by TEM/SEM and XRD to reveal the structural features and crystallographic phase. On the basis of the analysis of the time‐dependent evolution of ZnWO4 HHMs, a mechanism of in‐situ formation and crystallographic fusion, wherein the morphology, components, and phase changed, is proposed to explain the formation process of 3D hexagonal structures. Furthermore, calcined ZnWO4 HHMs were evaluated as anode material for lithium‐ion batteries, and exhibited better rate capabilities and cycling performance than the as‐synthesized material. This can be attributed to the stabilized and highly crystalline structure as well as the synergic and interfacial effects between different metal ions, which relieve the volume change during the charge/discharge process and provide more active sites for lithium‐ion storage. The synthetic method and growth mechanism could be applied to design and synthesize other hierarchical structures. Abstract : ZnWO4 hierarchical hexangular microstars (HHMs) composed of crossed microplatelets were synthesized by a two‐step hydrothermal reaction without using any surfactants. The excellent lithium‐storage ability of ZnWO4 HHMs is attributed to their unique structure.